Distal coronary embolization following acute myocardial infarction increases early infarct size and late left ventricular wall thinning in a porcine model. Issue 1 (December 2015) - Thomas, Reuben; Lim, Sang Yup; Qiang, Beiping; Osherov, Azriel; Ghugre, Nilesh; Noyan, Hossein; Qi, Xiuling; Wolff, Rafael; Ladouceur-Wodzak, Michelle; Berk, Thomas; Butany, Jagdish; Husain, Mansoor; et al.
Abstract Background Distal coronary embolization (DCE) of thrombotic material occurs frequently during percutaneous interventions for acute myocardial infarction and can alter coronary flow grades. The significance of DCE on infarct size and myocardial function remains unsettled. The aims of this study were to evaluate the effects of DCE sufficient to cause no-reflow on infarct size, cardiac function and ventricular remodeling in a porcine acute myocardial infarction model. Methods and results Female Yorkshire pigs underwent 60 min balloon occlusion of the left anterior descending coronary artery followed by reperfusion and injection of either microthrombi (prepared from autologous porcine blood) sufficient to cause no-reflow (DCE), or saline (control). Animals were sacrificed at 3 h (n = 5), 3 days (n = 20) or 6 weeks (n = 20) post-AMI. Cardiovascular magnetic resonance (CMR), serum troponin-I, and cardiac gelatinase (MMP) and survival kinase (Akt) activities were assessed. At 3d, DCE increased infarct size (CMR: 18.8 % vs. 14.5 %, p = 0.04; serum troponin-I: 13.3 vs. 6.9 ng/uL, p < 0.05) and MMP-2 activity levels (0.81 vs. 0.49, p = 0.002), with reduced activation of Akt (0.06 versus 0.26, p = 0.02). At 6 weeks, there were no differences in infarct size, ventricular volume or ejection fraction between the two groups, although infarct transmurality (70 % vs. 57 %, p < 0.04) and ventricular thinning (percent change in mid anteroseptal wall thickness:-25.6 % vs. 0.7 %, p = 0.03) were significantly increased in the DCE group. Conclusions DCE increased early infarct size, but without affecting later infarct size, cardiac function or ventricular volumes. The significance of the later remodelling changes (ventricular thinning and transmurality) following DCE, possibly due to changes in MMP-2 activity and Akt activation, merits further study.